Plasmatic Levels of Cytokines and Quality of Life among Elderly Individuals with Dizziness - Gislaine da Silva Moreira; Luciana Lozza de Moraes Marchiori; Daiane Soares de Almeida Ciquinato; Glória de Moraes Marchiori; Licia Sayuri Tanaka Okamura; Braulio Henrique Magnani Branco; Regina Célia Poli-Frederico (International Archives of Otorhinolaryngology)
Introduction Few studies have investigated the relationship between cytokines and dizziness in elderly individuals.